2014
DOI: 10.1016/j.pjnns.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of polymorphisms of genes encoding collagen IX and XI in lumbar disc disease

Abstract: The intervertebral disc disease (IDD) is one of the most common musculoskeletal disorders. A number of environment and anthropometric risk factors may contribute to it. The recent reports have suggested the importance of genetic factors, especially these which encode collagen types IX and XI. The allelic variants in the collagen IX genes - COL9A2 (Trp2) and COL9A3 (Trp3) have been identified as genetic risk factors for IDD, because they interfere the cross-linking between collagen types II, IX and XI and resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 14 publications
0
34
0
3
Order By: Relevance
“…It is estimated that the condition has approximately 75% heredity origin [12]. Genes that have been found to significantly increase risk of LDH include those encoding structural proteins, matrix metalloproteinases, apoptosis factors, growth factors, and single nucleotide polymorphisms in the vitamin D receptor gene resulting in inflammatory cytokine imbalance [11].…”
Section: Genetic Predispositionmentioning
confidence: 99%
“…It is estimated that the condition has approximately 75% heredity origin [12]. Genes that have been found to significantly increase risk of LDH include those encoding structural proteins, matrix metalloproteinases, apoptosis factors, growth factors, and single nucleotide polymorphisms in the vitamin D receptor gene resulting in inflammatory cytokine imbalance [11].…”
Section: Genetic Predispositionmentioning
confidence: 99%
“…Moreover, Rathod et al (2012) revealed that COL9A2 gene variation is a cause of this disease in the Indian population. However, Janeczko et al (2014) found no association between COL9A2 polymorphism and risk of intervertebral disc disease. In the present study, we found a significant correlation between COL9A2 sequence variation and risk of this condition in a Chinese population.…”
Section: Discussionmentioning
confidence: 81%
“…To date, several studies have tested the association between the COL9A2 gene and development of intervertebral disc disease in various populations (Annunen et al, 1999;Kales et al, 2004;Virtanen et al, 2007;Rathod et al, 2012;Janeczko et al, 2014). Annunen et al (1999) carried out an investigation involving 157 patients and 174 controls, identifying a COL9A2 genetic mutation that cosegregates with the disease phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen IX (COL9A2 and COL9A3) 31,32,[37][38][39]42,45,47,48,102,107,116,117) Collagen IX is a structural protein, which consists of the cartilage collagen II/IX/XI heteropolymer. Collagen IX is 31) .…”
Section: Aggrecan Genementioning
confidence: 99%